Improving Door-to-Needle Times for Acute Ischemic Stroke: Effect of Rapid Patient Registration, Moving Directly to Computed Tomography, and Giving Alteplase at the Computed Tomography Scanner. (January 2017) - Kamal, Noreen; Holodinsky, Jessalyn K.; Stephenson, Caroline; Kashayp, Devika; Demchuk, Andrew M.; Hill, Michael D.; Vilneff, Renee L.; Bugbee, Erin; Zerna, Charlotte; Newcommon, Nancy; Lang, Eddy; Knox, Darren; et al.
Abstract : Background—: The effectiveness of specific systems changes to reduce DTN (door-to-needle) time has not been fully evaluated. We analyzed the impact of 4 specific DTN time reduction strategies implemented prospectively in a staggered fashion. Methods and Results—: The HASTE (Hurry Acute Stroke Treatment and Evaluation) project was implemented in 3 phases at a single academic medical center. In HASTE I (June 6, 2012 to June 5, 2013), baseline performance was analyzed. In HASTE II (June 6, 2013 to January 24, 2015), 3 changes were implemented: (1) a STAT stroke protocol to prenotify the stroke team about incoming stroke patients; (2) administering alteplase at the computed tomography (CT) scanner; and (3) registering the patient as unknown to allow immediate order entry. In HASTE III (January 25, 2015 to June 29, 2015), we implemented a process to bring the patient directly to CT on the emergency medical services stretcher. Log-transformed DTN time was modeled. Data from 350 consecutive alteplase-treated patients were analyzed. Multivariable regression showed the following factors to be significant: giving alteplase in the CT (32% decrease in DTN time, 95% confidence interval [CI] 38%–55%), stretcher to CT (30% decrease in DTN time, 95% CI 16%–42%), patient registered as unknown (12% decrease in DTN time, 95% CI 3%–20%), STAT stroke protocol (11% decrease in DTN time, 95% CI 1%–20%), and stroke severity (National Institutes of Health Stroke Scale score 6–8: 19% decrease in DTN time, 95% CI 6%–31%; National Institutes of Health Stroke Scale score >8: 27% decrease in DTN time, 95% CI 17%–37%). Conclusions—: Taking the patient to CT on the emergency medical services stretcher, registering the patient as unknown, STAT stroke protocol, and administering alteplase in CT are associated with lower DTN time.